Applicability of equivalent linearization methods to irregular isolated bridges. (15th June 2017) - Jara, J.M.; Raya, G.; Olmos, B.A.; Martinez, G.
Highlights: Applicability of equivalent linearization methods. Isolated bridges with unequal pier heights. Pier displacement demands. Nonlinear analyses of medium-span RC bridges. Abstract: Equivalent linearization methods are widely applied to assess the seismic demands of buildings and bridges. Several regulation codes include methodologies to conduct linear analyses with equivalent structures. Normally, bridges are highly irregular structures due to the different pier heights. This study evaluates the applicability of a group of equivalent linearization methods proposed in the literature to predict the seismic response of isolated bridges with height irregularities. The isolation system is composed by lead rubber bearings. A parametric study is carried out in bridges with three types of height irregularities and combinations of relative height between piers. The bridges were subjected to a family of seismic records from a subduction zone to evaluate the equivalent elastic methods based on the results of nonlinear time-history analysis. Especial emphasis is devoted to assess the influence of the bridge irregularity on the ability of the methods to predict the nonlinear bridge demands. The results show the applicability of the equivalent linearization methods as function of the ductility demands and the height irregularity of the bridges. This study also discusses the parameter combinations that the different approaches lead to underestimate or overestimate the bridges demands.